KAJIAN REPARASI PENGECATAN PADA LAMBUNG KAPAL (STUDI KASUS KM. KIRANA 3) - Zulfaidah Ariany (Diponegoro University, 2014)
[Title: Study on Painting Repair of Hull Ship (Case Study of KM. Kirana 3)] Regular and scheduled maintenance are important things to make sure any ships could work and sail properly. So the main purpose to carry peoples or deliver the goods can be run smoothly. Painting is one of that items. It can protect the body or their parts from rust attack, in common word, corrosion. Estimating the paints consumption upon maintenances are very useful for ship owners, project owners neither shipyards. Upon ship KM. Kirana’s hull reparation, an analysis process can calculate the estimation of her paints consumption: For hull paint reparation of KM Kirana 3, it needed estimated 8 cane (20 liter) for bottom painting, 13 canes for bottom top, 42 canes for topside and 6 canes for weather and upper deck.